Heuristic battery-protective strategy for energy management of an interactive renewables–buildings–vehicles energy sharing network with high energy flexibility. (15th June 2020) - Zhou, Yuekuan; Cao, Sunliang; Hensen, Jan L.M.; Hasan, Ala
Highlights: Synergistic interactive energy frameworks for flexible district energy management. Cycling aging of chemical battery storages via a novel dynamic degradation model. Heuristic battery-protective strategy with smart grid-responsive charging scheme. Multi-criteria improvement with renewables, power exchanges and advanced strategies. Robust solutions for relative capacity improvement in interactive energy networks. Abstract: Interactive energy sharing networks with centralised coordinated energy management between buildings and vehicles can increase eco-economics viability, while tracking battery degradations is critical to the assessment of techno-economic performance and energy flexibility. In this study, a mathematical model was developed to characterise the cycling aging of electrochemical battery storage in multidirectional interactions within interactive renewables–buildings–vehicles energy sharing networks, with classification of the cycle life into two groups (slow degradation zone and acceleration zone). An advanced battery-protective energy control strategy was developed that fully utilises inherent battery depreciation characteristics for flexible energy management. Multi-criteria were investigated, including equivalent CO2 emissions, import cost, energy flexibility, and the equivalent relative capacity of battery storage. With respect to the advanced battery-protective energy control strategy, the grid-battery charging process can decrease the depth of discharge and thus slow down the battery depreciation rate, but it will also lead to an increase in the number of cycles along with cycling aging. The research results show that, in terms of cycling aging, the single-variable mathematical fitting method with piecewise fitting curves (correlation coefficient of 0.9807) is more accurate than the bivariate mathematical fitting method (correlation coefficient of 0.9206). In addition, the proposed battery-protective control strategy can contribute to multi-criteria improvement. Furthermore, robust solutions for relative capacity improvement have been proposed with a lower limitation of fractional state of charge at 0.7. This study formulated a synergistic interactive energy framework for flexible district energy management, involving complementary solar-wind renewable systems, static and mobile battery storage, diversified energy demands in district buildings, and an advanced battery-protective energy management strategy, which can provide technical guidance to designers, operators, and stakeholders in terms of flexible participation in smart and resilient district energy networks.